2004
DOI: 10.1038/sj.emboj.7600110
|View full text |Cite
|
Sign up to set email alerts
|

LKB1 is a master kinase that activates 13 kinases of the AMPK subfamily, including MARK/PAR-1

Abstract: We recently demonstrated that the LKB1 tumour suppressor kinase, in complex with the pseudokinase STRAD and the scaffolding protein MO25, phosphorylates and activates AMP-activated protein kinase (AMPK). A total of 12 human kinases (NUAK1, NUAK2, BRSK1, BRSK2, QIK, QSK, SIK, MARK1, MARK2, MARK3, MARK4 and MELK) are related to AMPK. Here we demonstrate that LKB1 can phosphorylate the T-loop of all the members of this subfamily, apart from MELK, increasing their activity 450-fold. LKB1 catalytic activity and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
1,295
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,230 publications
(1,356 citation statements)
references
References 55 publications
39
1,295
4
3
Order By: Relevance
“…Although AMPK, Sik2 and Mark2 have been proposed as major proximate regulators for Crtc2 (Lizcano et al, 2004;Dentin et al, 2007;Fu and Screaton, 2008;Hezel and Bardeesy, 2008), Sik1 has also been suggested as an important kinase inhibitor for Crtc1 transcriptional activity (Katoh et al, 2006). Further, SIK1 is a Crtc1/ cAMP/CREB target gene whose induction is proposed to phosphorylate and mediate a negative feedback loop on Crtc1 in neuronal cells .…”
Section: Discussionmentioning
confidence: 99%
“…Although AMPK, Sik2 and Mark2 have been proposed as major proximate regulators for Crtc2 (Lizcano et al, 2004;Dentin et al, 2007;Fu and Screaton, 2008;Hezel and Bardeesy, 2008), Sik1 has also been suggested as an important kinase inhibitor for Crtc1 transcriptional activity (Katoh et al, 2006). Further, SIK1 is a Crtc1/ cAMP/CREB target gene whose induction is proposed to phosphorylate and mediate a negative feedback loop on Crtc1 in neuronal cells .…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of AMPK and related kinases LKB1 has been termed a master kinase based on its ability to control the activity of the 14 members of the AMPK-related family of serine-threonine kinases through direct phosphorylation of a threonine residue in their activation loops (see Figures 1 and 2) (Lizcano et al, 2004). Cells lacking LKB1 have decreased activity of these AMPK family kinases whereas restoration of wild-type LKB1 rescues their catalytic activity.…”
Section: Biochemical Functions Of Lkb1mentioning
confidence: 99%
“…Physiologically, PAR1 kinases are activated by phosphorylation of the T-loop on a threonine residue. This phosphorylation is carried out by another serine/threonine kinase, LKB1 (Lizcano et al (2004); for review see Bardeesy et al, this issue). Germline loss-of-function mutations in the LKB1 gene are responsible for autosomal dominant Peutz-Jeghers syndrome, which is characterized by the development of benign hamartomatous polyps throughout the gastrointestinal tract (Hemminki et al, 1998).…”
Section: Function Of Par1 In Carcinogenesismentioning
confidence: 99%